Language development and language impairment a problem-based introduction - Fletcher, Paul 1943-; O'Toole, Ciara (Chichester, West Sussex, UK Wiley-Blackwell, 2016)
"Language Development and Language Impairment offers a problem-based introduction to the assessment and treatment of a wide variety of childhood language developmental disorders. Focuses for the most part on the pre-school years, the period during which the foundations for language development are laid Uses a problem-based approach, designed to motivate students to find the information they need to identify and explore learning issues that a particular speech or language issue raises Examines the development of a child's phonological system, the growth of vocabulary, the development of grammar, and issues related to conversational and narrative competence Integrates information on typical and atypical language development"--Provided by publisher.
"Offers a problem-based introduction to the assessment and treatment of a wide variety of childhood language developmental disorders"--Provided by publisher.
Preface -- 1. Overview -- 2. The first year of life -- 3. Sounds -- 4. Words -- 5. Combining words -- 6. Beyond the sentence -- Appendix 1. IPA consonant and vowel charts -- Appendix 2. Reliability and validity -- Appendix 3. Sensitivity and specificity -- Appendix 4. Techniques for exploring speech percepton in infants -- Appendix 5. Grammatical analysis using the LARSP profile -- Index.
Includes bibliographical references and index.
Keywords: Language disorders in children